Carbon black produced by plasma in benzene solution applied as the conductive agent in lithium secondary batteries. (5th March 2023) - Choi, Go Bong; Kim, Yoong-Ahm; Hong, Daeseon; Choi, Yunji; Yeon, Sun-Hwa; Park, Young-Kwon; Lee, Gyeong-Geun; Lee, Heon; Jung, Sang-Chul
Abstract: When producing hydrogen and carbon black from hydrocarbons using plasma, the economic feasibility must be ensured. In this study, the produced carbon black was heat-treated at various temperatures and applied as a conductive agent in lithium secondary batteries to evaluate its potential. When plasma was discharged into the benzene solution, carbon black particles (primary particles, 20–50 nm) were generated along with hydrogen gas, and were aggregated to grow secondary particles 400–500 nm in size. When carbon black was heat-treated, the crystallinity increased as the heat-treatment temperature increased, and multiple nanoshells in the form of pentagons or hexagons were formed by continuous long multi-graphene. Carbon black produced by heat treatment at 1500 °C showed the highest capacity and excellent charge/discharge characteristics, which was attributed to its high electrical conductivity and specific surface area. The carbon black prepared in this study could be a good candidate to replace commercialised Super-P in the future. Graphical abstract: Image 1 Highlights: Plasma was discharged to the benzene to produce hydrogen gas and carbon black particles. The primary carbon black particles were aggregated to constitute secondary structures. The heat-treated carbon black has improved electrical conductivity and crystallinity. The heat-treated carbon black was applied to the conductive agent of the lithium secondary battery. The capacity and charge/discharge characteristics of carbon black heat treated at 1500 °C were the best.